Peutz–Jeghers Syndrome: A Rare Genetic Cause of Intestinal Obstruction - Rana, Abunur Md Masud; Haque, Taufiqul; Dew, Kallol Chandra (Community Based Medical Journal, 2023)
Peutz–Jeghers syndrome (PJS) is a rare autosomal dominant disorder. The mutation is found in the serine threonine kinase (STK11)/ liver kinase B1 (LKB1) gene on chromosome 19. It impacts 1 out of 50000–200000 individuals. Clinical menifestations include hyperpigmented lesion in oral cavity, lips, fingertips and perianal region. Abdominal pain, Anaemia, Gastrointestinal (GI) bleeding, GI polyp, Intestinal obstruction (mostly due to intussusception) and malignancy are closely interlinked with the disease. We present a 21 years old lady with characteristic hyperpigmented lesions in lips and fingertips with multiple polyps in the GI tract. The patient was presented in general emergency department with abdominal pain and vomiting. Detail workout revealed the diagnosis as PJS. We have plotted the diagnosis according to the WHO criteria due to the lacking of genetic analysis facility. Patients with PJS are at high risk of intestinal and extraintestinal malignancy. Early diagnosis and polypectomy along with surveillance for recurrence may prolong cancer free lifetime. CBMJ 2023 January: Vol. 12 No. 01 P: 115- 120